Bahasa Inggris - Margareth Sunjoto (Ide dan Dialog Desain Indonesia (Idealog), 2022)
The conspicuity of traf ic signs is crucial, as their purpose is to give drivers with direction and information. The ef ectiveness and ef iciency of a traf ic sign is determined by its visibility, legibility, and veracity of information for observers. This study recruited primarily postgraduate students as participants. The assessment was conducted as part of a controlled experiment. Method used in this research is a controlled indoor experiment using a visual search task in which a random order of daytime and nighttime scenes are given within 200 milliseconds. Subjects were instructed to identify any visible signs at the scene. Four variables, including the size/distance of signs, the complexity of the background, the luminance contrast, and the color dif erence, were utilized. The results reveal that the size of the sign influences its conspicuity. Sign conspicuity is likewise af ected by luminance contrast, however it may have a greater ef ect at night. The results may also show that the impact of color dif erence between daylight and nighttime conditions is minimal. In as much as a portion of the parameter's value is based on visual evaluation, and the findings do not appear to have reached a statistically significant level, additional methodological refinement is required. Keyword: conspicuity, traf ic sign, complexity, urban are